1997
DOI: 10.1210/jcem.82.3.3819
|View full text |Cite
|
Sign up to set email alerts
|

I. Adrenal Cortex and Steroid 21-Hydroxylase Autoantibodies in Adult Patients with Organ-Specific Autoimmune Diseases: Markers of Low Progression to Clinical Addison’s Disease

Abstract: Adrenal cortex antibodies (ACA) were measured by immunofluorescence in 8840 adult patients with organ-specific autoimmune diseases without overt hypoadrenalism. Sixty-seven (0.8%) patients were ACA-positive, with the highest prevalence in those with premature ovarian failure (8.9%). Forty-eight ACA-positive and 20 ACA-negative individuals were enrolled into a prospective study. Antibodies to steroid 21-hydroxylases (21-OH), steroid 17 alpha-hydroxylase (17 alpha-OH) and cytochrome P450 side chain cleavage enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 9 publications
3
54
0
3
Order By: Relevance
“…Furthermore, a good agreement between the results of ACA (measured by indirect immunofluorescence) and 21-OH autoantibodies (Abs) indicates that 21-OH Abs are the major component of the ACA (56)(57)(58)(59)(60). Consequently, 21-OH/ ACA have been shown to be markers of progression towards overt AAD in ACA-positive adults and children as described above (31)(32).…”
Section: Adrenal Autoantigensmentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, a good agreement between the results of ACA (measured by indirect immunofluorescence) and 21-OH autoantibodies (Abs) indicates that 21-OH Abs are the major component of the ACA (56)(57)(58)(59)(60). Consequently, 21-OH/ ACA have been shown to be markers of progression towards overt AAD in ACA-positive adults and children as described above (31)(32).…”
Section: Adrenal Autoantigensmentioning
confidence: 92%
“…ACA have also been found in subjects without clinical AAD with a prevalence varying from 0.3% in patients with vitiligo to 48% in those with idiopathic hypoparathyroidism (31,32). It has been shown that the presence of complement-fixing ACA is a marker for a high risk of progression to clinical AAD (33).…”
Section: Aca In Patients Without Clinical Aadmentioning
confidence: 99%
See 3 more Smart Citations